Oxidação preferencial de CO em catalisadores à base de ouro : estudo do efeito do suporte e do método de síntese do catalisador - Miranda, Aline Rodrigues Lopes (2016)
The CO preferential oxidation reaction (PROX) is used in the purification of hydrogen streams for various applications. Since the discovery of improved catalytic properties of gold particles, at nanometer range, in the CO oxidation reaction at low temperature, Au catalysts have been the subject of numerous investigations of CO oxidation and PROX. Concerning the heterogeneous catalysis, the catalyst activity is determined by several factors: the nanoparticles size, the metal loading and dispersion, the nature and porosity of the support, and the metal/support interaction. To understand the dependence of the support and the influence of the synthesizing method on the material properties and catalytic performances, gold nanoparticles supported on three different oxides (CeO2, MnO2 and TiO2) were successfully synthesized by the deposition precipitation (DP) method, using urea, and modified polyol (MP) method, using PVP as surfactant and sodium borohydride as reducing agent. Additionally, Au/SiO2 was obtained by the DP method. Characterizations were performed to assess the crystallinity, the metal mass percentage, the reduction temperatures and the respective reducing gas consumptions of pure oxides and supported materials synthesized by both methods. In addition, microscopic pictures were obtained to evaluate the materials morphology and the gold nanoparticles diameter. The Au catalysts synthesized by the DP method presented smaller particle sizes as compared to catalysts obtained by the MP method. Catalytic evaluation of the CO oxidation and PROX reactions were performed using temperature ramp starting at room temperature up to 200 °C. As a comparative parameter, the ratio between the catalyst mass and the gas feed flow remained constant at 1 mg / 1 mL / min for all reactions. The results showed that Au supported on TiO2 prepared by the DP method presented complete CO conversion at room temperature, but with the simultaneous supply of H2, this catalyst tends to oxidize H2, decreasing the CO conversion activity. On the other hand, the Au/CeO2 catalyst prepared by the DP method presented activity up to about 200 °C for PROX and better selectivity towards the CO2 formation.